FACTORS AFFECTING SUSTAINABILITY REPORT DISCLOSURE AMONG IDX-LISTED MINING COMPANIES - Angela, Jocevine; Setijaningsih, Herlin Tundjung (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to analyze the effect of profitability, leverage, and Board Diversity on sustainability report disclosures in mining companies listed on the Indonesia Stock Exchange. The sampling method used purposive sampling technique. The sample was 15 mining companies in the 2019 to 2021 research period and 45 data were processed. The data was processed using E-views 12 software. The results showed that profitability positively influences sustainability report disclosures. On the other hand, leverage and board diversity do not affect the disclosure of the sustainability report.